Postoperative analgesia for cleft lip and palate repair in children - Reena; Kasturi Hussain Bandyopadhyay; Abhijit Paul (Wolters Kluwer Medknow Publications, 2016)
Acute pain such as postoperative pain during infancy was ignored approximately three decades ago due to biases and misconceptions regarding the maturity of the infant's developing nervous system, their inability to verbally report pain, and their perceived inability to remember pain. More recently, these misconceptions are rarely acknowledged due to enhanced understanding of the developmental neurobiology of infant pain pathways and supraspinal processing. Cleft lip and palate is one of the most common congenital abnormalities requiring surgical treatment in children and is associated with intense postoperative pain. The pain management gets further complicated due to association with postsurgical difficult airway and other congenital anomalies. Orofacial blocks like infraorbital, external nasal, greater/lesser palatine, and nasopalatine nerve blocks have been successively used either alone or in combinations to reduce the postoperative pain. Since in pediatric population, regional anesthesia is essentially performed under general anesthesia, association of these two techniques has dramatically cut down the risks of both procedures particularly those associated with the use of opioids and nonsteroidal anti-inflammatory drugs. Definitive guidelines for postoperative pain management in these patients have not yet been developed. Incorporation of multimodal approach as an institutional protocol can help minimize the confusion around this topic.